THE DIFFERENCE OF SALIVARY SECRETORY IMMUNOGLOBULIN A (sIgA) LEVEL BETWEEN MALE ASTHMATIC CHILDREN AND FEMALE ASTHMATIC CHILDREN - Elfira, Yenni; Titien Suprihati, Indah (Dentino, 2018)
Background: Asthma is chronic airway inflammatory disorder where mast cells, eosinophils, and T lymphocytes play important role.The symptoms include wheezing, recurrent cough, shortness of breath, and suppressed chest. The age prevalence of asthma children is quite high and increases annually. Asthma affects boys twice the rate of the asthma as girl. Asthmatic patients need local immunity and antibodies so infections that occur in the oral cavity as a result of inhalation medication use can be avoided. The antibody of the oral defense system is secretory immunoglobulin A (sIgA). Objective: To explain the difference in salivary sIgA levels in male asthmatic children and female asthmatic children.Methods: The study was conducted on 21 subjects of asthmatic children consisted of 11 male and 10 female with the age range 9-11 years. Saliva sampling was taken in RSKP Respira Bantul, then it was taken to Laboratory of Molecular Biology FK UGM for ELISA test. Saliva was taken by Spitting method for 1.5 mL and done in the morning from 8-11 hours. Subjects were not allowed to eat 1 hour prior to salivary taking. Anamnesis and clinical examinationwere performed to see the condition of oral cavity, social status, and nutritional status. Saliva measurementusing Anti-human sIgA ELISA kit (Elebscience). Data were analyzed using Independent T test. Results:The mean of sIgA level in males was 0.18 Ã 10 Â± 0.06 and females was 0.15 Ã 10 Â± 0.03. Based on the results of the Independent T test, it was found that the p value =0.283 (p> 0.05). Conclusion: There is no difference in sIgA levels between male and female patients.